From Normal Skin to Squamous Cell Carcinoma: A Quest for Novel Biomarkers. (23rd August 2016) - Voiculescu, Vlad; Calenic, Bogdan; Ghita, Mihaela; Lupu, Mihai; Caruntu, Ana; Moraru, Liliana; Voiculescu, Suzana; Ion, Alexandra; Greabu, Maria; Ishkitiev, Nikolay; Caruntu, Constantin
Abstract : Squamous cells carcinoma (SCC) is the second most frequent of the keratinocyte-derived malignancies after basal cell carcinoma and is associated with a significant psychosocial and economic burden for both the patient himself and society. Reported risk factors for the malignant transformation of keratinocytes and development of SCC include ultraviolet light exposure, followed by chronic scarring and inflammation, exposure to chemical compounds (arsenic, insecticides, and pesticides), and immune-suppression. Despite various available treatment methods and recent advances in noninvasive or minimal invasive diagnostic techniques, the risk recurrence and metastasis are far from being negligible, even in patients with negative histological margins and lymph nodes. Analyzing normal, dysplastic, and malignant keratinocyte proteome holds special promise for novel biomarker discovery in SCC that could be used in the future for early detection, risk assessment, tumor monitoring, and development of targeted therapeutic strategies.